Predictive Value of Mean Platelet Volume in Saphenous Vein Graft Disease - Kaya,Ugur (2018)
Abstract Objective: To determine whether mean platelet volume (MPV), platelet distribution width (PDW), and platelet count could be used as determinants of mortality following coronary artery bypass graft (CABG) surgery and patency of saphenous vein grafts (SVG). Methods: The records of 128 patients who underwent emergency or elective coronary angiography after CABG surgery, and who died at an early stage were retrospectively reviewed. Patients were divided into three groups as early death, no SVG disease (SVGD), and SVGD group. MPV, PDW, and platelet count were evaluated at different times. Results: MPV was significantly higher in the stenotic group than in the nonstenotic group (9.7±1.8 fl and 8.2±0.9 fl, P<0.05). The postoperative MPV ratio was found to be higher in the stenotic group when compared to the preoperative period (9.6±1.8 fl and 7.8±0.9 fl, P<0.05). MPV values were also found to be higher in patients who died during the early stage than in surviving patients (9.4±1.9 fl and 8.0±1.0 fl, P<0.05). There was no statistically significant difference regarding platelet count and PDW ratios between the early deaths group and surviving patients. An MPV value higher than 10.6 predicted SVGD with 85% sensitivity and 45% specificity; and an MPV higher than 7.9 predicted early death with 80% sensitivity and 68% specificity were observed. Conclusion: MPV may be a useful indicator for the prediction of SVGD and mortality following CABG surgery.